2011
DOI: 10.1590/s0103-507x2011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de um programa para redução de ruído em unidade de terapia intensiva neonatal

Abstract: Methods: NICU-HUSM professionals were initially contacted through informal interviews during the morning, afternoon and night shifts. Leaflets were delivered and posters were installed to raise awareness of the harmful effects of noise on neonates and professionals and to suggest behavioral changes to reduce noise levels. The suggestions included avoiding loud talking, careful handling of the incubator doors and keeping mobile phones on silent mode. One month later, questionnaires were used to assess behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
0
13
0
6
Order By: Relevance
“…Various studies have reported that either equipment-or humaninduced sounds ranked first as noise sources in the NICU (Nathan et al, 2008;Valizadeh, Hosseini, Alavi, Asadollahi, & Kashefimehr, 2013;Weich et al, 2011). In addition, the level of noise caused by equipment was higher in measured momentary noise levels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Various studies have reported that either equipment-or humaninduced sounds ranked first as noise sources in the NICU (Nathan et al, 2008;Valizadeh, Hosseini, Alavi, Asadollahi, & Kashefimehr, 2013;Weich et al, 2011). In addition, the level of noise caused by equipment was higher in measured momentary noise levels.…”
Section: Discussionmentioning
confidence: 96%
“…These precautions involve performing "quiet time" or "quiet hour" practices during every 8-h shift (Bremmer, Byers, & Kiehl, 2003;Nathan et al, 2008); reducing alarm sounds or setting them to vibration mode/using illuminated visual alarm systems; responding immediately when an alarm sounds and switching to silent mode if not used for the infant; placing washbasins far from infant cradles; and using plastic drawers instead of metal drawers (Krueger, Schue, & Parker, 2007;Nathan et al, 2008). In addition, it must be compulsory to speak in a low voice and limit bedside talking; incubator lids should not be slammed; furniture should not be dragged; not to place stuff on incubator; avoid shoes that make noise; use cell phones in silent mode; and regular noise level measurements should be made within the unit (Krueger et al, 2007;Weich, Ourique, Tochetto, & Franceschi, 2011). Apart from these, the role of training has been reported in reducing noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse dado demonstra a necessidade de reconfiguração do processo de formação desses profissionais, com introdução de tal conteúdo na matriz curricular. Essa alteração repercutirá na prática e na assistência prestada à população, visando melhores condições de trabalho dos profissionais, além de proporcionar segurança ao paciente 13,14 .…”
Section: I S C U S S ã Ounclassified
“…In professionals, the adverse effects of continuous exposure to noise also involves headache, hearing loss, confusion, low power of attention, irritability, burnout, job dissatisfaction and the professionals may be impaired in the performance of their functions (7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%